Efficiency of the heat sink of a solar air collector based on metal chips - Madaminov Javlonbek; Uzbekov Mirsoli; Boynazarov Bekzod; Mukhtorov Sherzod; Khusanboyev Abdulqosim; Arziyev Saydullo; Okhunjanov Zuhriddin (E3S Web of Conferences)
I The article discusses the efficiency of heat sinks of solar air heater collectors (SAHC), based on the use of metal shavings as an absorber. Various types of metal shavings, such as drainage, chipping and fracture, and their effect on the thermal efficiency of the SAHC are studied. The results of studies of various designs of air heaters using metal shavings and their comparative advantages compared to traditional flat heat sinks are presented. The principles of operation of SAHC with various absorber configurations, including corrugated surfaces and the use of small metal shavings, are outlined, and design features for increasing the efficiency of installations are described. Calculation methods and experimental data are presented that confirm the increase in efficiency due to an increase in the contact area and improved heat transfer. The main parameters influencing the thermal efficiency of the SAHC, such as the body size, tilt angle, ambient temperature and properties of the transparent coating, are considered. Calculations and analyses have been carried out showing that optimal opening angles of metal shavings and their combination with a corrugated surface significantly improve the absorption capacity and heat transfer in the solar heating system, which helps to increase the overall efficiency of solar air heating systems.